Kajian Psikoprofetik Atas Pemikiran Al-Ghozali Tentang Manusia - Mufidah, Luluk Indarinul; Aziza, Ilza Ma’azi (STAI Miftahul Ula Nganjuk, 2017)
Overview of humans attracting the attention of various branches of science, especially psychology to examine it more deeply. Starting from the notion of psychology as a science that examines human behavior, psychologists generally hold that the physical condition, psychological quality, and environmental situation, are the main determinants of behavior and style of human personality. Human is a creature that can never be completely understood, because they contain a very interesting mystery to study. In the world of Islamic thought, discussion about human beings is often found in philosophy and tasawuf (Sufism). Human according to al-Ghazali has a fixed and unchanging identity, which he calls with the term an-Nafs. Whereas the definition of soul is something that is inserted into the body, which manifests when the sperm enters the womb. Al-Ghazali who lived in medieval times could not be separated from the influence of his time in looking at everything related to humans. This is seen in his works either in the field of philosophy or Sufism many of which explore about humans. Al-Ghazalis thought was much influenced by previous thinkers such as Ibn Sina. Al-Ghazali used many terms from Ibn Sina like an-Nafs, ar-Ruh and al-Jism, and indirectly al-Ghazali has reinforced Ibn Sinas terms with the arguments of syara. The concept of human being is very important, because it includes parts and worldviews.